2022
DOI: 10.1155/2022/8063851
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Study on Risk Factors and Nutritional Status of Postoperative Infection in Patients Undergoing Abdominal Surgery

Abstract: In order to evaluate the risk factors of postoperative infection in patients undergoing abdominal surgery and the correlation with nutritional status, 143 patients admitted to our hospital for abdominal surgery from September 2020 to September 2021 are selected and analyzed. By collecting the clinical results and related pathological data of all patients, all patients are divided into the postoperative infection group (48 cases) and the noninfection group (95 cases) according to whether postoperative infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%